The role of teamwork on team performance in extreme military environments: an empirical study. Issue 5 (20th July 2020) - Meslec, Nicoleta; Duel, Jacco; Soeters, Joseph
Abstract : Purpose: The purpose of this study is to explore the extent to which teamwork (developed either during an initial training phase or during a subsequent deployment phase) is influenced by the nature of the team's environment (extreme vs non-extreme) and the extent to which teamwork is one of the explaining mechanisms for team performance. Design/methodology/approach: Data was collected from 60 teams at 2 time-points: training phase in The Netherlands or Germany and deployment phase (in locations such as Afghanistan and Bosnia-Herzegovina). Findings: This study's results indicate that when teams consider working in extreme environments, they develop higher levels of teamwork as compared to teams expecting to work in non-extreme environments. These differences remain stable also during the deployment phase, such that teams operating in extreme environments will continue to have higher levels of teamwork as compared to teams operating in non-extreme environments. Originality/value: With this study, the authors contribute to the teamwork quality research stream by empirically studying how teamwork quality develops in unique military contexts such as extreme environments. Studies in such contexts are relatively rare.